Bruised - Sarah Skilton (Amulet, 2014)
When Imogen, a sixteen-year-old black belt in Tae Kwon Do, freezes during a holdup at a local diner, the gunman is shot and killed by the police, and she blames herself for his death. Before the shooting, she believed that her black belt made her stronger than everyone else―more responsible, more capable. But now that her sense of self has been challenged, she must =541 ## Mua